Pengaruh Bantuan Modal dan Pendampingan terhadap Peningkatan Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Kasihan, Kabupaten Bantul The Effect of Capital Assistance and Mentoring on Increasing the Income of Micro, Small and Medium Enterp - Prakoso, Maliki Aji; Arum, Khorifah (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy and have the potential to improve community welfare. This study aims to see the effect of capital assistance and mentoring on increasing the income of Micro, Small and Medium Enterprises (MSMEs) in Kasihan District, Bantul Regency. The research methodology used in this research is a quantitative method. The data sources in this study are primary and secondary data derived from questionnaires, documentation, and other literature. The sample in this study were 31 MSMEs in Kasihan Subdistrict who had received capital assistance from the Bantul Regency Government. The data analysis technique used in this research is multiple linear regression analysis. The results showed that the capital assistance variable partially affected the variable of increasing MSME income in Kasihan Sub-district, Bantul Regency; the mentoring variable partially affected the increase in MSME income in Kasihan Sub-district, Bantul Regency, and the capital assistance and mentoring variables simultaneously affected the increase in MSME income in Kasihan Sub-district, Bantul Regency